Predation-risk effects of predator identity on the foraging behaviors of frugivorous bats - Breviglieri, C. P B [UNESP]; Piccoli, G. C O [UNESP]; Uieda, W. [UNESP]; Romero, G. Q. (Springer Nature, 2013)
Predators directly and indirectly affect the density and the behavior of prey. These effects may potentially cascade down to lower trophic levels. In this study, we tested the effects of predator calls (playbacks of bird vocalizations: Tyto alba, Speotyto cunicularia, and Vanellus chilensis), predator visual stimuli (stuffed birds) and interactions of visual and auditory cues, on the behavior of frugivore phyllostomid bats in the field. In addition, we tested if the effects of predation risk cascade down to other trophic levels by measuring rates of seed dispersal of the tree Muntingia calabura. Using video recording, we found that bats significantly decreased the foraging frequency on trees when a visual cue of T. alba was present. However, no stimuli of potential predatory birds, including vocalization of T. alba, affected bat foraging frequency. There was a change in bat behavior during 7 min, but then their frequency of activity gradually increased. Consequently, the presence of T. alba decreased by up to ten times the rate of seed removal. These results indicate that risk sensitivity of frugivorous phyllostomid bats depends on predator identity and presence. Among the predators used in this study, only T. alba is an effective bat predator in the Neotropics. Sound stimuli of T. alba seem not to be a cue of predation risk, possibly because their vocalizations are used only for intraspecific communication. This study emphasizes the importance of evaluating different predator stimuli on the behavior of vertebrates, as well as the effects of these stimuli on trait-mediated trophic cascades. © 2013 Springer-Verlag Berlin Heidelberg.
Keywords: Anti-predator behavior; Indirect interactions; Landscape of fear; Predator cues; Risk sensitivity; Top-down effects; Trait-mediated indirect effects; Vertebrates